Toxicity, permeability and drug-metabolizing enzyme activities of curcumin analogues - Yakubu, Ndatsu (2015)
Curcumin (a dietary polyphenolic compound) derived from turmeric (Curcuma longa) possesses potent biological activities. However, curcumin‘s clinical application is severely limited due to its rapid metabolism and poor bioavailability. Hence, two curcumin analogues, which are 2,6-bis(2,5-dimethoxybenzy-lidene)cyclohexanone (BDMC33) and 2,6-bis(2-fluorobenzylidene)cyclohexanone (MS65) with potent anti-inflammatory activities than curcumin were synthesized by our research group. To ascertain the toxicity,permeability and drug-metabolizing enzyme activities of BDMC33 and MS65, their in vitro toxicity test at (0-400 μM) on Caco-2 cells using MTT assay, the in vivo toxicity test on zebrafish embryos and larvae at (0-50 μM), and acute toxicity effects (0-30 μM) on adult male zebrafish were investigated for 5 hr, 5 days, and 48 hr of exposure, respectively. The sub-chronic toxicity (14 days of exposure) of aspirin (control) and both compounds (8, 10 and 20 μM), respectively, on adult male zebrafish and the histopathological examinations (transverse sections) of intestine and liver of adult male zebrafish using hematoxylin and eosin (H and E) staining were evaluated. The permeability effects of both compounds (50 μM) in differentiated Caco-2 cells after 180 min of exposure were measured based on its apparent permeability coefficient (Papp) values of the apical site (A) to basolateral site (B) and basolateral site (B) to the apical site (A) and also the absorption rates of both compounds (20 μM) on adult male zebrafish were also measured after 1-5 hr of exposure. Furthermore, the effect of both compounds on drug-metabolizing enzyme activities, which were NADPH-cytochrome p450 reductase (CPR), UDP-glucuronosyltransferase (UGT), glutathione-S-transferase (GST) and sulfotransferase (SULT) in differentiated Caco-2 cells and adult male zebrafish were measured using colorimetric methods. Similarly, toxicity, permeability effects and drug-metabolizing enzyme activities of curcumin (reference compound) and 3-(2-fluoro-benzylidene)-5-(2-fluorocyclohexylmethylene)-piperidin-4-one (EF-24) (positive control) in differentiated Caco2 and adult male zebrafish were conducted for comparison. The results showed that the 5 hr LC50 for all test compounds in Caco-2 cells were 50 μM, the 5 days LC50 values on zebrafish embryos and larvae were 6.25 μM (BDMC33), 12.5 μM (MS65), 5 μM (curcumin and EF-24), and the 48 hrs LC50 values on the adult male zebrafish were 20 μM (BDMC33 and MS65) and 10 μM (curcumin and EF- 24). The heartbeats of zebrafish larvae subjected to BDMC33 and MS65, separately, for 5 days were 113±0.05 min-1(BDMC33), 112±0.12 min-1 (MS65), 109.3±0.14 min-1 (curcumin), and 110±1.10 min-1 (EF-24), while that of the normal zebrafish larvae was 117±0.15min-1. The normal zebrafish embryos hatched after 2-3 days with >50% hatchability rates, which is similar to those exposed to <6.25 μM (BDMC33) and <12.5 μM (MS65) as compared to curcumin and EF-24 (<5 μM) treatments, separately. The results of the apparent permeability coefficient (Papp) in Caco-2 cells after 120 min incubation and their absorption (uptake) rates in adult male zebrafish after 4 hr suggested that MS65>BDMC33>EF-24>curcumin. The activities of drug-metabolizing enzymes (CPR,UGT, GST and SULT) in cells and adult male zebrafish subjected to all test compounds, separately, as compared to that of normal cells and zebrafish demonstrated that MS65 is better than BDMC33, followed by EF-24 and then curcumin. Therefore, both MS65 and BDMC33 could be potential lead compounds to address the problems and issues of rapid metabolism, and poor bioavailability of curcumin when consumed orally.